A self-reported screening tool for detecting community-dwelling older persons with frailty syndrome in the absence of mobility disability: the FiND questionnaire. - Matteo Cesari; Laurent Demougeot; Henri Boccalon; Sophie Guyonnet; Gabor Abellan Van Kan; Bruno Vellas; Sandrine Andrieu (PLoS ONE, 2014)
BACKGROUND: The "frailty syndrome" (a geriatric multidimensional condition characterized by decreased reserve and diminished resistance to stressors) represents a promising target of preventive interventions against disability in elders. Available screening tools for the identification of frailty in the absence of disability present major limitations. In particular, they have to be administered by a trained assessor, require special equipment, and/or do not discriminate between frail and disabled individuals. Aim of this study is to verify the agreement of a novel self-reported questionnaire (the "Frail Non-Disabled" [FiND] instrument) designed for detecting non-mobility disabled frail older persons with results from reference tools. METHODOLOGY/PRINCIPAL FINDINGS: Data are from 45 community-dwelling individuals aged ≥60 years. Participants were asked to complete the FiND questionnaire separately exploring the frailty and disability domains. Then, a blinded assessor objectively measured the frailty status (using the phenotype proposed by Fried and colleagues) and mobility disability (using the 400-meter walk test). Cohen's kappa coefficients were calculated to determine the agreement between the FiND questionnaire with the reference instruments. Mean age of participants (women 62.2%) was 72.5 (standard deviation 8.2) years. Seven (15.6%) participants presented mobility disability as being unable to complete the 400-meter walk test. According to the frailty phenotype criteria, 25 (55.6%) participants were pre-frail or frail, and 13 (28.9%) were robust. Overall, a substantial agreement of the instrument with the reference tools (kappa = 0.748, quadratic weighted kappa = 0.836, both p values<0.001) was reported with only 7 (15.6%) participants incorrectly categorized. The agreement between results of the FiND disability domain and the 400-meter walk test was excellent (kappa = 0.920, p<0.001). CONCLUSIONS/SIGNIFICANCE: The FiND questionnaire presents a very good capacity to correctly identify frail older persons without mobility disability living in the community. This screening tool may represent an opportunity for diffusing awareness about frailty and disability and supporting specific preventive campaigns.